Parasitosis intestinal y condiciones higiénico - sanitarias en estudiantes de octavo a décimo grado de la Unidad Educativa Adolfo Valarezo. - Jiménez Yaguana, Jennifer Alina (2024)
Geohelminthiasis or intestinal parasitosis, classified as infections of the digestive system, are among the ten main causes of death in Ecuador and affect pediatric ages to a greater extent as they have a susceptible immune system and undefined hygiene habits. The lack of environmental sanitation, inadequate food sanitation and poor personal hygiene are the main focus of intervention for the eradication of parasitosis because they are conceived as a risk factor. The present investigation focused on determining the existence of intestinal parasitosis and the hygienic-sanitary conditions in students from eighth to tenth grade of the Adolfo Valarezo Educational Unit, period September 2022 - March 2023; A study was developed with a quantitative, descriptive, observational and transversal approach, the universe was made up of 540 students and the sample was made up of 123 who met the inclusion criteria. To collect information, coproparasitic analysis of fecal samples was carried out and an adaptation of the National Intestinal Parasitism Survey was applied, which identified the different hygienicsanitary conditions predisposing to intestinal parasitosis. After data processing and analysis, the following results were obtained: the general prevalence of intestinal parasitosis in the study population was 43.09%; of these parasitized students, 24.39% are in inadequate sanitary conditions; Likewise, it was identified that 41.46% have poor hygiene. In the correlation of the variables, it was determined that there is statistical significance between students who present intestinal parasitosis with inadequate hygienic conditions; However, there is no relationship with inadequate sanitary conditions. Therefore, it is concluded that there is a high proportion of parasitized students, mostly male, who remain in inadequate hygienic conditions. To this end, prevention activities for soil-transmitted helminth infections and health promotion activities were carried out to improve the sanitation and hygiene of the institution